Mechanisms of prospective memory performance: exploring depression-related impairments in metamemory, cue detection, and intention retrieval - Rice, Michaela S., author; Davalos, Deana, advisor; Thomas, Michael, committee member; Faw, Meara, committee member; Karoly, Hollis, committee member (Colorado State University. Libraries, 2025)
Prospective memory (PM) is a critical cognitive skill describing our ability to create and perform future-intentioned goals. College students require a high level of PM abilities to complete their assignments for school, attend work and class regularly, and balance their social life with studying and personal care. PM can be divided into its two subcomponents: cue detection and intention retrieval, which can be measured using electroencephalogram/event-related potentials (EEG/ERPs). Impairments in PM may be explained or predicted by variations in these specific neurophysiological components. Metamemory, or how an individual thinks of their own memory abilities, may predict overall PM performance; metamemory guides how an individual encodes their intended future goal, monitors the environment for the cue, and sets reminders to complete their goal. Since the components of PM are necessary to successfully perform a PM goal, and metamemory may interact with the neurocognitive underpinnings of PM, metamemory beliefs may also predict cue detection and intention retrieval. Further, metamemory beliefs and the neurocognitive components of PM may be sensitive to psychological disorders, such as depression, which could impact overall PM performance. Depression is a particularly prevalent and debilitating disorder, especially among college students, and could play a role in these various factors involved in PM. This dissertation is made up of three papers that examine the neural and cognitive mechanisms involved in the relationship between depression and PM. The first paper characterizes how metamemory beliefs predict the neural and behavioral components of PM. The second paper assesses how depression levels predict the neural components of PM and metamemory beliefs. Further, Study 2 assesses how the relationship between depression and the neural components of PM varies based on metamemory beliefs. Finally, the third paper builds on Studies 1 and 2 by examining how depression levels relate to behavioral PM performance, and if metamemory beliefs or the neural components of PM may explain or contribute to this relationship. Altogether, this dissertation clarifies the cognitive, neural, and psychological factors that may support or harm PM skills, which could help inform intervention strategies to strengthen and protect future-oriented goal setting abilities.
Keywords: depression; metamemory; cue detection; prospective memory; intention retrieval